FROM FARM TO TABLE: EMPOWERING WOMEN FARMERS THROUGH RED CHILI PRODUCT DOWNSTREAMING IN DALUNG VILLAGE, SERANG CITY - Gunawan, Panji; Ningsih, Tawaffaona; Susyanti, Fani Yulia; Anisah, Anisah; Puspa, Rani; Nurasiah, Iis; Lasmawati, Siti Dewi Kutria (Yayasan Education and Social Center, 2025)
This community engagement program focuses on empowering the Women Farmer Group (Kelompok Wanita Tani/KWT) in Dalung Village, Serang City, Indonesia, by enhancing their skills in processing red chili harvests through downstream product strategies. The program involved comprehensive training sessions covering product processing techniques, attractive packaging, basic financial management, and digital marketing skills. Collaboration between Universitas Bina Bangsa students participating in Kuliah Kerja Mahasiswa (KKM) and the KWT members facilitated knowledge transfer and practical application. The initiative aims to increase the added value of red chili products, thereby boosting income for women farmers. Additionally, it supports the economic empowerment of rural women and strengthens the sustainability and independence of micro, small, and medium enterprises (MSMEs) in the area. By improving product quality and marketing reach, this program contributes to rural development and the enhancement of local agribusiness competitiveness.